My fine fellow - Cohen, Jennieke (HarperTeen, 2022)
Helena Higgins is at the top of her class at the Royal Academy, and she is prepared to become a successful culinarian, a culinary consultant for society's elite. Penelope Pickering wants to prove to the English elite that her Filipino cuisine can compete with European standards. When Helena and Penelope meet Elijah Little, a Jewish street vendor who cannot own a shop due to his religion, Helena decides to help turn him into a gentleman chef.